Nutrient uptake, use efficiency and yield of rice as influenced by time of transplanting and nitrogen levels - Devi, Sunita; Sharma, Neetu; Sharma, B C; Sharma, Vikas; Chand, Guredev; Sharma, Bupesh (ORYZA-An International Journal of Rice, 2019)
An experiment was conducted during Kharif, 2016 to investigate the influence of transplanting dates and nitrogen levels on productivity of transplanted fine rice. Experiment was laid out in factorial randomized block design with two  transplanting dates (i.e. D1-15th and D2-30th July) as one factor and four levels of nitrogen (i.e. 0, 30, 60 and 90 kg N/ha) as second factor. Time of transplanting did not influence growth, yield attributes and yield. However, among different levels of nitrogen, significantly highest yield and yield attributes were recorded with 60 kg N/ha. Significantly highest straw yield was recorded with 90 kg N/ha. Rice transplanted on 15th July proved to be superior with respect to gross returns (Rs.70337.50/ha), net return (Rs.38259.28/ha) and B: C ratio (1.19) to that of 30th July transplanting. Whereas among nitrogen levels highest gross returns (Rs.79307.50/ha), net returns (Rs.52314.96) and B: C (1.94) ratio were obtained with application of 60 kg N/ha.